An Analysis of the Impact of Regional Taxes, Social Assistance Expenditures, and Income Inequality on Economic Growth in Regencies/Cities in Aceh Province - Yunidar Purnama Sari; Hefrizal Handra; Efa Yonnedi (Transpublika Publisher, 2024)
This study aims to analyze the impact of regional taxes, social assistance expenditures, and income inequality on the economic growth of regencies/cities in Aceh Province for the 2020-2023 period using a panel regression model. The analysis results indicate that regional taxes have a positive and significant impact on economic growth, where increased regional taxes contribute to the development of critical infrastructure and public services. Furthermore, social assistance expenditures also enhance household purchasing power, which directly boosts local economic growth. However, income inequality has a negative and significant impact on growth, as rising inequality hinders public access to education and healthcare and creates social instability. These findings underscore the importance of effective management of regional taxes and social assistance programs, as well as the need for policies to reduce income inequality as a strategy to promote inclusive and sustainable economic growth in Aceh. This study provides recommendations for local governments to formulate more progressive policies in managing economic resources for the welfare of society.